Infrastructure and Public Utilities Privatization in Developing Countries - Auriol, Emmanuelle; Picard, Pierre M. (World Bank, Washington, DC, 2012)
The paper analyzes governments' tradeoff between fiscal benefits and consumer surplus in privatization reforms of noncompetitive industries in developing countries. Under privatization, the control rights are transferred to private interests so that public subsidies decline. This benefit for tax-payers comes at the cost of price increases for consumers. In developing countries, tight budget constraints imply that privatization may be optimal for low profitability segments. For highly profitable public utilities, the combination of allocative inefficiency and critical budgetary conditions may favor public ownership. Finally, once a market segment gives room for more than one firm, governments prefer to regulate the industry. In the absence of a credible regulatory agency, regulation is achieved through public ownership.